Bacteriological Examination on Bottled Water - Mukhiya, Rajnarayan; Thapa, Puja; Shakya, Shrawasti; B.K, Soniya; Nepal, Rupa; Shrestha, Ram Krishna; Thakur, Rajesh Kumar (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Bottled water are the packaged drinking water available commercially and manufactured by the company after treatment techniques like UV light, reverse osmosis or distillation, chlorination and carbon filtration etc. which are supposed to reduce the bacterial contamination to the safe level. Water-related diseases are of great concern in developing countries like Nepal. Every year, there are countless morbidity and mortality due to the consumption of unsafe drinking water. Recently, there have been increased uses of bottled drinking water in an assumption that the bottled water is safer than other sources of water and its use will help to protect from water related diseases. So, the main objective of this study was to analyze the bacteriological quality of bottled drinking waterMethod: A community based cross-sectional study was conducted on bottled drinking water. A total of 60 bottled drinking water samples were collected for microbiological examination for the detection of total coliforms via membrane filtration technique followed by inoculation on M- endo agar and heterophilic count by pour plate method in Nutrient agar. The bacterial growth in these medium were counted as CFU/100ml and CFU/ml respectively. The bacteria growth were identified by colony morphology, inoculation on biochemical medium and Gram stainingResults: Among total 60 samples, 48(80%) were positive for bacterial growth and 12(20%) revealed no bacterial growth. 35(58.33%) samples were contaminated with coliforms. Similarly, among total 60 samples, 48(80%) samples were contaminated with heterophiles.Conclusion: more than half of the bottled water showed bacterial growth in terms of both coliform and heterotrophs. Presence of coliforms indicate fecal contamination and lack of proper processing.